Fracture Characteristics and Disaster-Causing Mechanism of Rock Strata Based on Arch Mechanical Model of Plane Contact Block - Zhang Xin-chao; Du Feng; Tang Jun-hua; Wang Qin-ting; Lu Fei-fei (Geofluids)
The 52307 working face with large mining height in Daliuta coal mine is chosen as the research background, where there is the special mining condition in the overburden structure with a buried depth of more than 150 m and only one layer of key structure in Shendong mining area. Using the methods of similarity simulation experiment and theoretical analysis, the overburden movement law based on the arch mechanical model of plane contact block is systematically researched. The research results indicate that before the initial weight, the main key layer appears layered fracture in the mining process, and its lower rock layer becomes a part of the collapse zone. Before the initial weight, the upper key layer forms a “fixed supported beam” structure. When the beam reaches the limit length, shear failure occurs in the middle position; during the periodic weight, the upper key layer breaks into the plane contact block arch structure close to the same size. Relying on the friction between the contact planes, it has a certain displacement but does not collapse completely. The load transmitted from overburden is transmitted to the rear of the gob through the semiarch characteristics of the structure; the sliding instability and rotary deformation instability of the plane contact block arch structure are analyzed. The fracture of the key layer lags behind the mining position of the working face by a certain distance, due to the influence of the fracture angle of collapse zone in the advancing process of working face. The research results provide an important guiding significance for prediction and prevention for dynamic disaster of rock strata in working face with large mining height.